Poor glycemic control is associated with the risk of subclinical hypothyroidism in patients with type 2 diabetes mellitus - Jaeho Cho; Jung Bin Kim; Jun Ho Lee; Il Rae Park; Jun Sung Moon; Ji Sung Yoon; In‐Kyu Lee; Kyu Chang Won; Hyoung Woo Lee (2016)
Overt hypothyroidism is frequently found in patients with type 2 diabetes mellitus (T2DM), but it remains unknown the relationship between subclinical hypothyroidism (SCH) and T2DM. We attempt to evaluate the difference in prevalence of SCH between patients with T2DM and general population, and the association between SCH and glycemic control status ofdiabetic patients. This was cross-sectional study. Total 8,528 subjects who visited for health check-up were recruited. SCH was defined as an elevated level of serum thyroid stimulating hormone (> 4.0 mIU/L) with a normal level of free thyroxine. T2DM group was categorized into three groups by glycosylated hemoglobin (HbA1c): < 7% (reference), ≥ 7% and < 9%, ≥ 9%. Finally, 7,966 subjects were included. The prevalence of SCH was not different between healthy controls and subjects with T2DM (8.1% vs. 7.4%, p = 0.533; in men, 5.7% vs. 5.1%, p = 0.573; in women, 10.9% vs. 11.7%, p = 0.712), but it was increased with highest HbA1c group more than well controlled group, especially in women. The risk of SCH was increased by group with poorer glycemic control; the odds ratio for HbA1c ≥ 9% compared to < 7% was 2.52 (95% confidence interval [CI], 1.09 to 5.86; p = 0.031), and 4.58 (95% CI, 1.41 to 14.87; p = 0.011) in women, but not significant in men. The prevalence of SCH was similar between T2DM and healthy group. Poor glycemic control in T2DM was obviously associated with the risk of SCH, especially in elderly women. These results suggest SCH as comorbidity may be considered in elderly women with poor glycemic control.